An investigation into the design of a deployment strategy for Lean Enterprise: the case of a Consumer Packaging Manufacturing Company. - Valsamakis, Vassilis (2013)
This dissertation details an applied research into the design, development and deployment of of a strategy for Lean Enterprise in a manufacturing company which is a market leader in the consumer packaging industry. The research draws upon knowledge and experience documented in related literature, and carries out extensive field work in the particular company to develop an appropriate strategy. To provide the context for this research, an overview of the organisation’s journey in becoming a Lean Enterprise to-date is presented. The research draws upon knowledge areas including Lean Six Sigma, Change Management, Performance Measurement, and Balanced Scorecard Strategy mapping and execution, in order to develop the theoretical basis for the development of the strategy. Data collection and analysis enables understanding and evaluation of the effectiveness and efficiency of deployment to-date, supports the identification of critical success factors in the particular organisational context, and forms the basis for the design, development and deployment of the strategy. Preliminary results from the deployment are being discussed and evaluated in order to provide evidence of the effectiveness of the strategy. Conclusions are drawn and wider implications are discussed.